2013
DOI: 10.3171/2013.7.spine1328
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory failure from Surgifoam expansion after anterior cervical surgery

Abstract: A 65-year-old woman underwent an uneventful C3–4 anterior cervical discectomy and fusion for a large, symptomatic disc herniation. On postoperative Day 1 the patient suffered a sudden, acute respiratory compromise. Emergency fiberoptic intubation revealed significant anterior neck swelling with concern for physical obstruction of the airway. Computed tomography of the neck did not demonstrate an expanding hematoma. The patient was managed with surgical wound exploration and washout. Examination of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Moreover, it has been suggested that it is bactericidal for multiple strains (5 (17). In all of these four cases, neurological signs and symptoms worsened and reoperations were performed one day after surgery like in our case.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, it has been suggested that it is bactericidal for multiple strains (5 (17). In all of these four cases, neurological signs and symptoms worsened and reoperations were performed one day after surgery like in our case.…”
Section: Discussionmentioning
confidence: 87%
“…Subsequently, this would have led to obstruction of one or more mucous glands causing formation of a mucocele. Alternatively, expansion of the Surgifoam following injection could have led to progressive swelling, as has been described in anterior cervical fusion . Finally, although Surgifoam is a commonly used substance for injection laryngoplasty in adults, no study has specifically evaluated the use of this particular injectate in children.…”
Section: Discussionmentioning
confidence: 99%
“…Although endoscopic closure with use of CO 2 laser has been commonly used in repair of laryngeal clefts, injection laryngoplasty is being implemented with increasing frequency. This technique has been shown to decrease symptoms in patients with type I laryngeal cleft, and it is commonly used as an initial surgical intervention for patients with this condition at our institution. Complications from this procedure are infrequent, and there are essentially no reports of complication rates within the currently available literature.…”
Section: Introductionmentioning
confidence: 99%
“…Airway compromise in the postoperative period can occur due to factors extrinsic or intrinsic to the larynx. Extrinsic compression following the anterior approach to the cervical spine may happen due to soft tissue swelling, hematoma or accumulation of cerebrospinal fluid (CSF) or hemostatic agents 3,4 . Intrinsic obstruction may happen due to laryngeal swelling, vocal cord paralysis, local trauma secondary to intubation (such as arytenoid cartilage dislocation), laryngospasm or increased secretions 3,5 .…”
Section: Introductionmentioning
confidence: 99%